Considerations, benefits and unintended consequences of banning plastic shopping bags for environmental sustainability: A systematic literature review - Muposhi, Asphat; Mpinganjira, Mercy; Wait, Marius (SAGE Publications, 2022)
Although the ban on plastic bags is gaining in prominence as a policy option to manage plastic bag litter, there are mixed views on its rationale and effectiveness. This study employs a systematic literature review to understand considerations, benefits and unintended consequences of banning plastic bags. The review’s results pointed to the limited success of a plastic bag ban owing to lack of suitable alternatives, limited state capacity to monitor and enforce the ban, thriving black market, structural and instrumental power of the plastic industry. The power of the industry was manifested by the covert practice of deflecting accountability to consumers by focusing on business-oriented solutions, including an inclination towards self-regulation. The findings of this study underscored the need for a global treaty to address the transient nature of plastic bag litter and moving away from the symbolic gesture of targeting only plastic shopping bags but considering the environmental impact of all forms of plastic such as straws, foamed plastics, plastic bottles and caps. There is a general consensus in literature that the end of plastic shopping bags is not nigh due to their utilitarian benefits. This study therefore recommends the promotion of a circular economy focusing on ecological modernisation, sustainable plastic bag manufacturing and recovery strategies such as recycling as a long-term strategy. A significant strand of literature reviewed also recommends the adoption of community-driven approaches such as voluntary initiatives as opposed to a plastic bag ban as they proved to be effective in promoting environmental citizenship behaviours in countries such as Finland.